Analisis Kinerja Perusahaan Sebelum Dan Sesudah Initial Public Offering (IPO) Di Bursa Efek Indonesia (BEI) (Studi Kasus Pada Perusahaan Non Keuangan yang IPO Di Bursa Efek Indonesia Pada Tahun 2012 Dan 2013) - Yuliarni, Teti; Maryati, Ulfi; Ihsan, Hidayatul (Jurusan Akuntansi Politeknik Negeri Padang, 2016)
This research aims to know the difference of the company before and after initial public offering at the indonesian stock exchange. The variables in this research are ROA (Return on Assets), OCF (Operating Cash Flow), SG (Sales Growth), TATO (Total Asset Turn Over), CFRS (Cash Flow Return on Sales), and CFNI (Cash Flow to Net Income). The sample of this research consist of 34 companies with purposive sampling method which is non financial company listed on the indonesian stock Exchange in IPO period 2012 - 2013. Analysis technique used is the method of analysis test different ( paired t test ) uses software ibm spss version 20. The results showed that (1) To the ratio of roa , sg and a tato there was a gap in the performance of which is significant at the company before and after ipo. (2) While to the ratio of ocf , cfrs and cfni there is no significant difference on corporations before and after ipo.